Implementation of Design Thinking Method in Visual Communication Design - Novena Ulita; Brian Alvin Hananto (Green Publisher Indonesia, 2022)
Design methodology is an important knowledge for student designers when doing design. However, in application in the design studio class, student designers often override this methodological aspect. This happens without realizing that students always have difficulty when asked to explain their work plans and the progress of their design work. With the methodology, student designers can more easily parse their work steps and convey their thinking ideas in a design concept when designing designs, especially visual communication designs (DKV). This journal aims to be able to describe the implementation of design methods in design design (DKV) so that it can describe logical and systematic thinking processes and work processes. Student designers can be able to apply and carry out correctly and present design design projects (DKV) in a responsible and professional manner so that it becomes an experience for them when they enter the world of work. With the theory of design methods and design thinking methods, the author reviews the application of design methods carried out at the two universities collaborating in this research project, namely Mercu Buana University and Pelita Harapan University. This research found the importance of methodological aspects in building motivation & design logic, the need to rearrange the curriculum structure according to the taxonomy of undergraduate education, the stages of work on the design report that are not in accordance with the work process in the design method used, and find the design thinking formula that is applied. on the DKV design.